2006
DOI: 10.2164/jandrol.106.000232
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Binding of Sperm With Superior Volume Regulation to Oviductal Epithelium

Abstract: ABSTRACT:The plasma membrane is a key organelle with respect to sperm fertilizing ability. A sensitive way of testing plasma membrane functionality is to examine the sperm ability to moderate its swelling in response to hypo-osmotic stress (volume regulatory ability) using an electronic cell counter to assess cell volume changes. In this study of frozen-thawed bull sperm, we examined the relationship among sperm-oviductal epithelium binding capacity, osmotically induced swelling response, volume regulatory abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…It is suspected that, in mammals, DNA-damaged spermatozoa are impaired to fertilize under natural conditions by the high selective pressure occurring in the female tract and during sperm-egg recognition (Holt & Van Look 2004, Khalil et al 2006, Satake et al 2006, Suarez & Pacey 2006, Rodriguez-Martinez 2007, Yeates et al 2009). These selection mechanisms are related to sperm structures that could also be modified in spermatozoa carrying damaged DNA Fertilization with DNA-damaged spermatozoa (Tarin et al 2000, Andrabi 2007, Thomson et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suspected that, in mammals, DNA-damaged spermatozoa are impaired to fertilize under natural conditions by the high selective pressure occurring in the female tract and during sperm-egg recognition (Holt & Van Look 2004, Khalil et al 2006, Satake et al 2006, Suarez & Pacey 2006, Rodriguez-Martinez 2007, Yeates et al 2009). These selection mechanisms are related to sperm structures that could also be modified in spermatozoa carrying damaged DNA Fertilization with DNA-damaged spermatozoa (Tarin et al 2000, Andrabi 2007, Thomson et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, it has been suggested that the strong selective process undergone by sperm in the female tract (by elimination of defective spermatozoa, sperm competition, cryptic female choice, etc.) is probably unrelated to a DNA-scanning mechanism, and that some kind of link between sperm phenotype and genotype could be involved in this process (Holt & Van Look 2004, Khalil et al 2006, Satake et al 2006, Suarez & Pacey 2006, Rodriguez-Martinez 2007. Hourcade et al (2010) showed that selection of DNA-undamaged spermatozoa occurs in mice during the transit through the oviduct as well as during the contact with the vitelline membrane, but this selective process is dependent on the source of sperm damage and probably related to the presence of damage in other cell structures.…”
Section: Introductionmentioning
confidence: 99%
“…Immaturity of sperm, therefore, may be associated with incomplete function of the sperm plasma membrane, which impairs binding to the oviductal epithelium, e.g., by a failure of interaction between protein/carbohydrate-binding sites on the sperm surface and glycosylated ligands on the oviductal epithelium. (Khalil et al 2006). Whereas cytoplasmic droplets present a quite common sperm abnormality in boar ejaculates, the incidence of chromatin instability seems to be relatively low in commercial boar semen (López-Fernández et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…12,75 Flagellar angulation occurs at the site of the cytoplasmic droplet, as it does in the infertile mice, proving that the ejaculated spermatozoa had retained their droplets. The infertility of spermatozoa with droplets has been suggested to reflect poor adherence to the zona pellucida (cows 72 ) and the oviductal epithelium (sows 76,77 ). As spermatozoa with retroflected flagella swim 'backwards' (head against the direction of travel 78 ), it is equally likely that their passage through mucus or the uterotubal junction is hampered and the oocyte is never reached, as is the case for the c-ros KO mice.…”
Section: Cytoplasmic Droplets: Post-ejaculatory Retention and Infertimentioning
confidence: 99%